FEV1 Is a Better Predictor of Mortality than FVC: the PLATINO Cohort Study - Menezes, Ana Maria B. (2014)
Objective: To determine whether the presence of chronic obstructive lung disease (COPD) and reduction of lung function parameters were predictors of mortality in a cohort.Materials/Patients and Methods: Population based cohorts were followed in Montevideo, Santiago and São Paulo during 5, 6 and 9 years, respectively. Outcomes included all-cause, cardiovascular, respiratory and cancer mortality; exposures were COPD, forced expiratory volume in one second (FEV1) and forced vital capacity (FVC). Cox regression was used for analyses. Sensitivity, specificity, positive and negative predictive values, receiver operator characteristics curves and Youden's index were calculated.Results: Main causes of death were cardiovascular, respiratory and cancer. Baseline COPD was associated with overall mortality (HR = 1.43 for FEV1/FVC<LLN; 2.01 for GOLD 2-4; 1.46 for GOLD 1-4; 1.50 for FEV1/FEV6 <LLN). for cardiovascular mortality, significant associations were found with GOLD 2-4 (HR = 2.68) and with GOLD 1-4 (HR = 1.78) for both genders together (not among women). Low FEV1 was risk for overall and respiratory mortality (both genders combined). FVC was not associated with overall mortality. for most COPD criteria sensitivity was low and specificity high. the area under the curve for FEV1 was greater than for FVC for overall and cardiovascular mortality.Answer to the Question: COPD and low FEV1 are important predictors for overall and cardiovascular mortality in Latin America.